Origin of Cancer: An Information, Energy, and Matter Disease - Hanselmann, Rainer G.; Welter, Cornelius (Frontiers in Cell and Developmental Biology, 2016)
Cells are open, highly ordered systems far away from equilibrium. For that reason, the first function of any cell is to prevent the permanent threat of disintegration described by thermo-dynamic laws and to preserve highly ordered cell characteristics like structures, cell cycle and metabolism. In that context, three basic categories play a central role - energy, matter and information. Every single of these three categories is equally important to the cell and depends on the others reciprocally. For that reason, we suggest that either energy loss (e.g. by disturbed mitochondria) or disturbance of information (e.g. mutations, aneuploidy) or changes in matter composition or exposition (e.g. micro-environmental changes, toxic agents) can irreversibly disturb molecular mechanisms leading to increased local entropy of cellular functions and structures. In terms of physics, changes to these normally highly ordered reaction probabilities lead to a biologically irreversibly, imbalanced but thermodynamically more stable state. This primary change independent of the initiator now provokes and drives a complex interplay between energy availability, matter exposition and increasing information disturbance depending on reactions that try to overcome or stabilize this intra-cellular, irreversible disorder described by entropy. Because the return to the original ordered state is not possible due to the thermodynamic reasons cells die, or persist in an meta-stable state and enter into a self-driven adaptive and evolutionary process that generates progressive, disordered cells resulting in a broad spectrum of progeny with different characteristics, and maybe one day one of these cells will show an autonomous and aggressive behavior – a cancer cell.